The Effect of Financial Performance on Stock Price Changes in Financial Sector Companies Listed on the Indonesia Stock Exchange - Dwiyanti, Heni; Imronudin, Imronudin (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Stock price fluctuations reflect market reactions to various factors, including company financial performance, economic conditions and investor sentiment. Understanding these factors is important for making better investment decisions. This study seeks to analyze the effect of financial performance on fluctuations in stock prices. Financial performance is assessed by the Debt-to-Equity Ratio (DER), Dividends Per Share (DPS), Earnings Per Share (EPS), and Dividend Payout Ratio (DPR). This study's population consists of financial sector enterprises listed on the Indonesia Stock Exchange (IDX) in 2023. A sample of 31 companies was obtained by purposive sampling. The data analysis employed multiple linear regression, the coefficient of determination, F-test, T-test, as well as classical assumption tests, all done using Eviews14 software. The data analysis results indicate that DER exerts a negative and minor influence on stock price fluctuations, but EPS, DPS, and DPR demonstrate a positive, also a substantial impact on stock price variations.